Type I AIE photosensitizers: Mechanism and application. Issue 2 (13th July 2021) - Li, Jianqing; Zhuang, Zeyan; Zhao, Zujin; Tang, Ben Zhong
Abstract: Photodynamic therapy (PDT) with plenty of advantages is expected to become a promising modality for cancer treatment, but challenges still remain. In the past decade, abundant photosensitizers (PSs) with aggregation‐induced emission (AIE) property make the development of PSs enter upon a new phase, offering incomparable merits. Recently, Type I AIE PSs with capability of generating radical reactive oxygen species (ROS) have emerged as strong candidates to overcome the inherent hypoxia nature of solid tumors. In this review, detailed discussions on the mechanisms of PDT are drawn to highlight the basic advantages of Type I pathway over Type II one in hypoxic PDT, followed by a summary of frequently‐used detection methods for the accurate distinguishing of the nature of ROS. Finally, the latest representative advances are summarized, and future perspectives of Type I AIE PSs are discussed. Abstract : Photodynamic therapy (PDT) is emerging as a promising cancer therapeutic treatment and receiving increasing interests. Focusing on this specific theme, this review presents a detailed introduction on the PDT mechanism, summarizes the detection methods for the nature of reactive oxygen species, and discusses the superiority of Type I photosensitizers with aggregation‐induced emission (AIE) property. At last, the latest advances on Type I AIE photosensitizers are reviewed.